Indonesia's national identity: Students, character education, and national challenges - Aris Riswandi Sanusi; Aim Abdulkarim; Cecep Darmawan; Syaifullah Syaifullah (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2026)
This study investigates how students at Universitas Buana Perjuangan Karawang comprehend and internalise Indonesian national identity amidst the pervasive challenges of globalisation and modernisation. In higher education, students are expected not only to master academic competencies but also to cultivate robust moral character as future custodians of the nation. Consequently, this research aims to analyse students' conceptualisation of national identity, evaluate the implementation of character education within campus life, and explore the contemporary socio-cultural challenges confronting the younger generation. Employing a qualitative methodology, data were collected through in-depth interviews, participant observation, and a comprehensive literature review. The findings reveal that students possess nuanced understandings of national identity, predominantly conceptualising it in terms of the core values of Pancasila, diversity, and mutual cooperation. Furthermore, the implementation of character education demonstrates positive outcomes when integrated into extracurricular activities, student organisations, and community service programmes. Nevertheless, substantial challenges persist, primarily driven by foreign cultural hegemony, rising individualism, and identity crises exacerbated by the digital era. Ultimately, this study recommends reinforcing character education grounded in local wisdom, revitalising Pancasila values within the curriculum, and promoting digital literacy that aligns with the Indonesian national character.